2020
DOI: 10.1093/cid/ciaa963
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram for Assessing Survival in Patients With COVID-19 Pneumonia

Abstract: Abstract Background The outbreak of coronavirus disease (COVID-19) in 2019 has spread worldwide and continues to cause great threat to peoples’ health as well as put pressure on the accessibility of medical systems. Early prediction of survival of hospitalized patients will help the clinical management of COVID-19, but such a prediction model which is reliable and valid is still lacking. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 33 publications
3
73
0
9
Order By: Relevance
“…In COVID-19 patients, elevated NLR on admission was reported to be signi cantly associated with disease severity 13,14 To date, a few prognostic models of COVID-19 have been developed. Dong et al found that hypertension, higher NLR and increased NT-proBNP value were signi cantly poorer prognostic factors in hospitalized COVID-19 patients 21 . A nomogram for predicting 14-day and 21day probability of in-hospital survival based on the three factors was developed, with high c-index and AUC in both training and validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, elevated NLR on admission was reported to be signi cantly associated with disease severity 13,14 To date, a few prognostic models of COVID-19 have been developed. Dong et al found that hypertension, higher NLR and increased NT-proBNP value were signi cantly poorer prognostic factors in hospitalized COVID-19 patients 21 . A nomogram for predicting 14-day and 21day probability of in-hospital survival based on the three factors was developed, with high c-index and AUC in both training and validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we could not validate their tree-model in our discovery dataset, but our prediction forest model achieved considerable accuracy (AUC 87%) in Yan's dataset. Notably, Dong et al built a predictive nomogram by using only three indicators: hypertension, neutrophil-to-lymphocyte ratio and NT-proBNP at admission to hospital, which surprisingly achieved 89.2% of C-index in internal validation set [13]. However, NT-proBNP is usually examined in patients with symptoms of cardiac dysfunction rather than regularly measured at admission, which may limit its application.…”
Section: Discussionmentioning
confidence: 99%
“…We identi ed 11 laboratory measures at admission which appear to associate with the poor COVID-19 outcomes. Among the regularly measured laboratory indicators at admission, the high neutrophil count, low lymphocyte count, high neutrophil-to-lymphocyte ratio, high direct bilirubin, and elevated lactate dehydrogenase have previously been identi ed as prognostic predictors for an unfavorable outcome [12,13,22,23]. However, in our discovery set, these predictors were not ranked at the top of VIS list for all candidate factors possibly because all patients in our study had progressed to severe or critical disease and the previous predictors may be less prognostic for severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging parameters including severe chest X-ray radiographic abnormalities and diffuse pulmonary infiltration on CT that have also been linked to severe disease. One multiparametric model aimed at predicting the risk of hospitalisation with an area under the curve (AUC) of 0.9, 66 while three studies aimed at predicting survival with AUC between 0.879 and 0.955, [67][68][69] and two other aimed at predicting disease mortality with AUC between 0.871 and 0.975. 70 71 Other algorithms were developed, aiming at predicting disease progression towards a severe phenotype with AUC from 0.77 to 0.9.…”
Section: Platelets Endothelial Dysfunction and Thrombosis And Sars-cmentioning
confidence: 99%